A comparative study of the impact of playing surface on the playing style of the top-five ranked tennis players in the world / Hazim Asyraf Zainor ... [et al.] - Zainor, Hazim Asyraf; Mohamed, Muhamad Noor; Mazaulan, Mardiana; Abu Kassim, Nurul Ain; Raja Hussein, Raja Nurul Jannat; Syed Mud Puad, Sharifah Maimunah (Universiti Teknologi MARA, 2023)
Mastering diverse tennis court surfaces demands distinct skills and strategies, enhancing adaptability for players to excel. Adapting to these differences not only shapes a well-rounded player but also offers a competitive edge by aligning tactics with conditions, opponents, and situations. Through purposive sampling, the study selected the top five global tennis players based on their 2022 ATP Tour Rankings. Analyzing match videos using NacSport Basic+ across clay (N=14), grass (N=14), and hard courts (N=10), the study scrutinized shot selection. Indicators included total serves, aces, success rates in serves, forehand, backhand, and volley shots, unforced errors for each type, and double faults. On hard courts, players achieved a mean of 75.50 ± 15.967 successful serves from 123.10 ± 28.192 attempts. Forehand shots averaged 20.40 ± 9.252 winners and 15.00 ± 6.018 unforced errors. Volleys saw 5.80 ±1.989 winners and only 1.40 ± 1.075 unforced errors, while backhand shots had more unforced errors (17.30 ± 7.134) than winners (10.30 ± 4.572). Transitioning to grass, the total serves won averaged 74.86 ± 18.068 out of 122.10 ± 30.105 attempts. Forehand shots-maintained prominence with 20.93 ± 7.290 winners and 20.07 ± 7.405 unforced errors. Volleys averaged 6.64 ± 3.608 for winners and 2.86 ± 1.099 unforced errors, with backhand shots showing more unforced errors (19.79 ± 5.508) than winners (12.00 ± 5.189). On clay, players achieved 71.93 ± 18.568 successful serves from 144.27 ± 43.645 attempts. Forehand shots averaged 20.40 ± 6.874 winners and 18.13 ± 7.745 unforced errors. Volleys saw 6.00 ± 2.449 winners and 2.07 ± 1.163 unforced errors, with backhand shots exhibiting more unforced errors (17.27 ± 5.898) than winners (10.53 ± 4.291). In essence, top players strategically adapt their style to each court's demands, leveraging strengths to excel. This adaptability underscores their exceptional skill and versatility, solidifying their positions as elite tennis players across diverse conditions.